Gk with Derek the ultimate general knowledge and quiz compendium: 1 history and geography - O'Brien Derek (Penguin Books, 2004)
Gk with Derek the ultimate general knowledge and quiz compendium: 1 history and geography / O'Brien Derek. -- New Delhi: Penguin Books, 2004 001 Obr13 v1 No. of Copies : 2